Improving enzymatic hydrolysis of wheat straw using ionic liquid 1-ethyl-3-methyl imidazolium diethyl phosphate pretreatment - Li, Qiang; He, Yu-Cai; Xian, Mo; Jun, Gao; Xu, Xin; Yang, Jian-Ming; Li, Liang-Zhi (Bioresource technology, 2009)
This study aims to establish a cellulose pretreatment process using ionic liquids (ILs) for efficient enzymatic hydrolysis. The IL 1-ethyl-3-methyl imidazolium diethyl phosphate ([EMIM]DEP) was selected in view of its low viscous and the potential of accelerating enzymatic hydrolysis, and it could be recyclable. The yield of reducing sugars from wheat straw pretreated with this IL at 130 °C for 30 min reached 54.8% after being enzymatically hydrolyzed for 12 h. Wheat straw regenerated were hydrolyzed more easily than that treated with water. The fermentability of the hydrolyzates, obtained after enzymatic saccharification of the regenerated wheat straw, was evaluated using Saccharomyces cerevisiae. This microbe could ferment glucose efficiently, and the ethanol production was 0.43 g/g glucose within 26 h. In conclusion, the IL [EMIM]DEP shows promise as pretreatment solvent for wheat straw, although its cost should be reduced and in-depth exploration of this subject is needed.